METAETIKA KAIP ROMANTIZMO FORMA - Jokubaitis, Alvydas (Problemos, 2013)
Straipsnis skiriamas metaetikos kritikai. Tai bandymas pagilinti Ronaldo Dworkino kritiką, kuri kai kuriais atžvilgiais yra ribota ir nenuosekli. Šis autorius mano, kad metaetika yra tam tikras etikos variantas, tačiau neatskleidžia jos turinio. Dworkinas teisus sakydamas, kad metaetiką formuoja Apšvietos epistemologinės prielaidos, tačiau jis nemato, kad už to stovi ir romantizmas. Metaetika gali būti aiškinama kaip romantinio mąstymo forma. Pagal nusistovėjusį požiūrį, ši disciplina dažniausiai siejama su Apšvieta. Straipsnio tikslas – įrodyti romantiškas metaetinio mąstymo prielaidas.Metaethics as a Form of RomanticismAlvydas JokubaitisSummaryThis paper presents a critique of metaethics. It is an attempt at deepening the critique proposed by Ronald Dworkin, which is in some respects limited and inconsistent. Dworkin is right in saying that metaethics is based on the epistemological premises of the Enlightenment, but it has to be pointed out that he overlooks the influence of Romanticism. Metaethics can be understood as a form of romantic thinking. There is a widespread consensus according to which this discipline is linked with the ideas of the Enlightenment. The aim of this paper is to prove that metaethics is based on premises which are romantic.Philosophers doing metaethics cut off all links between established concepts, revolt against common sense, retreat into a realm of ideas, strive for novelties and originality, get lost between incompatible viewpoints and antinomies. They want to find something new and unexpected behind daily phenomena. Works of metaethics are different from impressionistic pieces of art, but their guiding attitude is the same. The main difference is that the artists do not deny their relationship with Romanticism, whereas philosophers doing metaethics never openly talk of such relations. Metaethics is a disguised form of Romanticism. The principle that Carl Schmitt called “subjectified occasionalism” is operational in both cases.